MODEL OF MANAGEMENT OF PROCESSES AND PHENOMENA’S IN THE MILITARY SECURITY SYSTEM (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
This paper presents theoretical analyzes and assessments of governance models in the military security system in the context of dynamically changing national security. The model for managing processes and phenomena in the system has been studied.